Improved Tolerance to a New Amino Acid-Based Formula by Infants with Cow's Milk Protein Allergy - Pipop Jirapinyo (2018)
© 2016 American Society for Parenteral and Enteral Nutrition. Background: Prevalence and severity of cow's milk protein allergy (CMA) in infants are increasing. A proportion of infants with CMA still elicit signs and symptoms of CMA while ingesting commercial amino acid-based formulas (AAFs). We propose that protein in glucose polymers (GPs) derived from corn starch in the AAFs might be the cause of intolerance to AAF in some infants. We thus have produced small molecules of GPs from rice starch, eliminating the protein fraction from them, and subsequently used them as the sole source of carbohydrate in a new amino acid-based formula (NAAF). Methods: The efficacy of the NAAF was compared with that of an AAF in a double-blind, placebo-controlled food challenge (DBPCFC) in young infants with CMA aged <4 months. Infants consumed each formula for 14 days before switching to the other one. If no respiratory, dermatologic, and gastrointestinal symptom occurred, it was considered tolerance. After the challenge, infants consumed the tolerated formula for 4 weeks to prove real tolerance to that formula. Results: Of 46 infants, 23 were intolerant to the AAF, of whom 7 (30.4%) were also intolerant to the NAAF. Sixteen of the 23 infants who were intolerant to the AAF could tolerate the NAAF (P <.05). The minimal important difference of decreasing percentage of intolerance to the NAAF was 34.8% compared with the infants who were intolerant to the AAF. Conclusion: The NAAF is better tolerated than a commercially available AAF for the management of infants with CMA.